VD_FINDINFO HC / 2014 / 613 vom 10. Juni 2014 - VD Tribunal cantonal (2014)
SUCCESSION LÉGALE, LIBÉRALITÉ, RAPPORT SUCCESSORAL, RÉDUCTIONEN GÉNÉRAL, VENTE, DONATION MIXTE | 475 CC, 527 ch. 1 CC, 527 ch. 3 CC, 626 CC